2017
DOI: 10.1063/1.4974460
|View full text |Cite
|
Sign up to set email alerts
|

A noise-resistant ADSA-PH algorithm for superhydrophobic surface’s static contact angle evaluation

Abstract: The blur around the contact points significantly decreases the evaluated static contact angle for superhydrophobic surface which is clearly presented in the paper. To improve the accuracy in the evaluated static contact angle for superhydrophobic surface, an accurate static contact angle algorithm, namely ADSA-PH (axisymmetric drop shape analysis-profile and height), is proposed. It discards the extracted drop edge points close to the contact points and makes use of the residual points and the drop height to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…51 It has been shown that for superhydrophobic surfaces with contact angles approaching 1801 error in determined contact angles can be up to 51 even when subpixel resolution is used. 30 The errors in contact angle produced by one-pixel displacement of the baseline To demonstrate the importance of correct positioning of the baseline, we simulate a one-pixel baseline shift from an actual baseline position. We perform numerical simulations described above, and the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…51 It has been shown that for superhydrophobic surfaces with contact angles approaching 1801 error in determined contact angles can be up to 51 even when subpixel resolution is used. 30 The errors in contact angle produced by one-pixel displacement of the baseline To demonstrate the importance of correct positioning of the baseline, we simulate a one-pixel baseline shift from an actual baseline position. We perform numerical simulations described above, and the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29] The choice of the image analysis algorithm is important since different algorithms give different values of contact angles. 30,31 Contact angle goniometry, as a technique that utilizes image processing, is prone to substantial inaccuracies for superhydrophobic surfaces (y 4 1501). 32 The area close to the three-phase contact line is distorted or blurred due to optical errors, [33][34][35] leading to systematic errors in the determination of the droplet shape and tangent line (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contact angle measurements using the sessile drop technique depend on the experience and skills of the user. There are large deviations even if an experienced user performs the measurements [44]. Vuckovac et al have shown that errors increase for superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%